An Example of Microwave Holography Investigation of an Old Orthodox Russian Icon Dated to 19th Century - Sergey I. Ivashov; Vladimir V. Razevig; Dmitriy L. Sergeev; Alexander S. Bugaev; Feng Zhou; Elena I. Prokhanova; Anastasia V. Shcherbakova; Sergey N. Dobrynin; Maxim Vasilenkov (Heritage, 2022)
The study, preservation and restoration of the cultural heritage objects of mankind are not only of great cultural importance but also have a significant economic component because cultural values of past centuries attract tourists from all over the world. The use of modern technical and scientific achievements in the field of non-destructive testing makes it possible to obtain new knowledge about cultural objects regarding their origin and dating, as well as to contribute to their better restoration and preservation. An important component of their use is additional opportunities to identify high quality fakes of original cultural objects that have historical significance. The capabilities of various non-destructive testing (NDT) methods used to examine cultural objects are characterized by their penetration depth, resolution, and sensitivity to material properties. Thus, in many cases, it is necessary to perform multi-sensor non-destructive testing and creating large data sets that require an efficient evaluation. This article considers an example of using microwave (MW) holographic sensors for the examining of an old Orthodox Russian Icon dated of the late 19th century. The paper describes the technology of microwave holography, which has recently been applied to the examination of art works. Unlike the well-studied X-ray method, MW holography makes it possible to examine objects with one-sided access. Its other advantages are the relative cheapness of the equipment and the safety of use due to the low level of radiation. The article describes a MW holograms reconstruction algorithm, as well as a method for improving the quality of obtained MW images. The data collected at MW research of the Icon are compared with the results of X-ray examination and confirmed by subsequent opening and visual examination performed by professional restorers.